Negotiating identities : states and immigrants in France and Germany - Kastoryano, Riva (Princeton studies in cultural sociology., 2002)
The author analyzes interactions between states and immigrants in the US, France and Germany. The observations are built into a model of "negotiations of identities" and extended to consider how the EU affects identities negotiated at national levels.